City Anamorphoses in Measure for Measure - Sophie CHIARI (E-REA)
Measure for Measure is a dark tragicomedy unusually set in a Central European city, a place which works as a palimpsest characteristic of Shakespeare’s geographical ambiguities. The playwright uses Italian sources, resorts to commedia dell’arte devices, gives his characters Italian names, and as is often the case with his other Italian plays, endows Italy with a certain sense of freedom as opposed to Vienna, where sexual behavior is about to be strictly regulated. But rather than consider the submerged Italian background of Measure for Measure as evidence of authorial revision, this article argues that Vienna makes sense in the play and that Shakespeare, in offering several distorted perspectives on his city, was clearly influenced by the visual arts of his time. In this attempt to resort to new, unexpected ingenious effects, he worked out an experimental, anamorphic geography intended to reproduce an ambivalent map of love, where unabashed sexual licence is confronting repressed desire. Indeed, just like Holbein’s Ambassadors which switches from a grand vision of power and knowledge to that of a disquieting skull, Measure for Measure shows a passage from ducal palace to the margins of the city which foregrounds whores and hangmen as well as syphilitic bodies and skeletons.